Transformation of the Authority of Religious Courts in the Indonesian Judicial System - Eka putra zakran; Maya Surya (ISNU Sumatera Utara, 2026)
The Religious Courts are a key institution in the Indonesian judicial system, handling specific cases for Muslims, including marriage, inheritance, waqf, and Sharia-compliant economic disputes. Along with national social and legal developments, the authority of the Religious Courts has undergone significant transformation, reflecting the adaptation of Islamic law to contemporary needs. This study aims to analyze the history of the formation, development, and implications of strengthening the authority of the Religious Courts over Islamic law in Indonesia. The method used is normative legal research with a statutory, historical, and conceptual approach, through a literature review of laws, Supreme Court regulations, academic literature, and primary sources of Islamic law. The results show that the authority of the Religious Courts has expanded from handling family and inheritance cases to encompass the management of waqf and the resolution of Sharia-compliant economic disputes, including Sharia-compliant banking transactions and business contracts. This transformation affirms the legitimacy of Islamic law within the national system, expands public access to justice, enhances the professionalism of judges, and generates relevant contemporary Islamic legal precedents. In conclusion, strengthening the authority of the Religious Courts not only increases the effectiveness of the institution in upholding Sharia principles but also strengthens the integration of Islamic law into the national legal system. Research recommendations emphasize the need to improve the capacity of judges, harmonize Islamic and national legal regulations, and develop digital mechanisms and Sharia-based mediation to expand Religious Court services effectively and fairly.